Bisecting GlcNAc modification of vesicular GAS6 regulates CAFs activation and breast cancer metastasis - Jing Li; Xueting Ren; Lin Cao; Kaixiang Min; Meng Wang; Shuai Lin; Lei Lei; Zengqi Tan; Xiaoliang Cheng; Xiang Li; Feng Guan (Cell Communication and Signaling)
Abstract Background Cancer-associated fibroblasts (CAFs) are a pivotal component of the tumor microenvironment (TME), playing key roles in tumor initiation, metastasis, and chemoresistance. While glycosylation is known to regulate various cellular processes, its impact on CAFs activation remains insufficiently explored. Methods We assessed the correlation between bisecting GlcNAc levels and CAFs markers (α-SMA, PDGFRA, PDGFRB) in breast cancer tissues. The effects of small extracellular vesicles (sEVs) derived from MDA-MB-231/OEvec and MDA-MB-231/OEMGAT3 cells on CAFs activation were examined using western blotting, transwell, and collagen contraction assays. Proteomic analysis was performed to identify dysregulated proteins in sEVs from different cell lines. The role of GAS6 in CAFs activation was validated through in vitro and in vivo experiments. The impact of bisecting GlcNAc modification on GAS6 expression and function was analyzed through protein degradation and N-glycosylation site mutation. The effect of activated CAFs on breast cancer metastasis was evaluated using western blotting and transwell assays. Results We found that low bisecting GlcNAc levels were associated with CAFs activation within the TME of breast cancer. Breast cancer-derived sEVs stimulated the conversion of normal fibroblasts to CAFs, with GAS6 in sEVs playing a key role by interacting with AXL receptors on fibroblasts. Introducing GAS6 into normal fibroblasts induced their conversion into CAFs, which enhanced breast cancer cell metastasis. Notably, GAS6 was decorated with bisecting GlcNAc, which promoted its degradation in donor cells, leading to reduced GAS6 levels in sEVs and attenuating GAS6-mediated CAFs activation. Conclusion Taken together, our findings provide new insights into the functional role of bisecting GlcNAc on GAS6-mediated CAFs activation in breast cancer.